HOW DIGITALISATION AFFECTING EMPLOYEES WELL-BEING DURING COVID-19 OUTBREAK: A META-ANALYSIS STUDY - Shella Azzahra; Sasha Nabila Ayunanda; Euphrasia Susy Suhendra (Jurnal Ilmiah Ekonomi Bisnis, 2022)
The COVID-19 pandemic is having a profound impact, with far-reaching impacts on the way people live and work around the world. The increasing digitization of the workplace during this pandemic has led to changes in working conditions, which can be a risk factor for decreased well-being and performance. Due to the social distancing requirements of the pandemic, workers have experienced a transformative change in working conditions with the rapid adoption of digital technology. The aim of this research is to conducted a literature study to explain especially how digital technology or digitization can affect employees well-being during the COVID-19 outbreak. The research method used is a literature study using 25 reviewed journals that published from 2019-2021. Research findings identify adverse psychosocial effects on the well-being of employees affected by digitalization during the COVID-19 outbreak, including: technostress, work stress, workload, anxiety, burnout, fatigue, and isolation.